1989
DOI: 10.1136/jme.15.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Which of two individuals do you treat when only their ages are different and you can't treat both?

Abstract: A relative value of life dependent on age has been produced from a survey of 721 randomly selected individuals together with other observations of professional practice. The results are presented in diagrammatic form. If two identical people, except for age, present for medical treatment for a life-threatening condition and only one can be treated then the diagram indicates what the choice should be.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 3 publications
7
62
0
Order By: Relevance
“…Johannesson and Johannsson report undiscounted weights for life years gained at ages 30, 50 and 70 of 1.0; 0.22; and 0.1, respectively [40]. Lewis and Charny show that respondents have a very strong preference for 5 year olds over 70 year olds, a strong preference for 35 year olds over 60 year olds and a slight preference for 8 year olds over 2 year olds [41].…”
Section: Qaly Maximisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Johannesson and Johannsson report undiscounted weights for life years gained at ages 30, 50 and 70 of 1.0; 0.22; and 0.1, respectively [40]. Lewis and Charny show that respondents have a very strong preference for 5 year olds over 70 year olds, a strong preference for 35 year olds over 60 year olds and a slight preference for 8 year olds over 2 year olds [41].…”
Section: Qaly Maximisationmentioning
confidence: 99%
“…There is empirical evidence that some people (but by no means a clear majority) wish to give less priority to those who are considered to be in some way responsible for their ill health [30,36,41,42,48]. In the Gallup Poll in August 1994, 41% of respondents wanted lower priority for those with self-inflicted illnesses.…”
Section: Qaly Maximisationmentioning
confidence: 99%
“…Studies based on choice scenarios in life-saving contexts show a marked preference favouring children and young adults over elderly people. Lewis and Charney found that 80% of people interviewed in the UK thought that 35 year olds should have priority over 60 year olds in receiving life-saving treatment [10]. Tamura et al found that a majority of Japanese thought younger patients should receive priority over older ones for emergency operations.…”
mentioning
confidence: 98%
“…Discounting, widely used in an attempt to reflect time preferences, works under the presumption of a linear social time preference; that is, that the value of health diminishes at a constant rate over time. It is unclear how much this applies to health states, but the little empirical evidence available suggests that time, rather than having a linear effect on the desirability of good health, seems to have an uneven effect, increasing and decreasing through life stages (Lewis and Charny 1989;Wright 1986). Benefit-cost analyses, which assign dollar values to health benefits ($2 million per life saved, for example), are likely to fail when we consider the issue of discounting benefits.…”
Section: Cost-utility Analysismentioning
confidence: 96%